2014
DOI: 10.1177/2325967114542775
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Symptomatic Olecranon Traction Spurs

Abstract: Background:There is a paucity of information pertaining to the pathoanatomy and treatment of symptomatic olecranon traction spurs.Purpose:To describe the pathoanatomy of olecranon traction spur formation, a technique for spur resection, and a series of patients who failed conservative care and underwent operative treatment.Study Design:Case series; Level of evidence, 4.Methods:Eleven patients (12 elbows) with a mean age of 42 years (range, 27-62 years) underwent excision of a painful olecranon traction spur af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…24 Olecranon spurs form within the superficial portion of the central triceps tendon insertion and protrude posteriorly, sometimes with a slight upward curve. 2,14 The spurs can become quite large, and 1 study found that they occupy 30% to 50% of the triceps insertion in patients with triceps tendonitis. 14 This contrasts with olecranon osteophytes, which are located on the posterolateral or posteromedial articular border on the tip of the olecranon (Fig.…”
Section: Anatomymentioning
confidence: 99%
See 4 more Smart Citations
“…24 Olecranon spurs form within the superficial portion of the central triceps tendon insertion and protrude posteriorly, sometimes with a slight upward curve. 2,14 The spurs can become quite large, and 1 study found that they occupy 30% to 50% of the triceps insertion in patients with triceps tendonitis. 14 This contrasts with olecranon osteophytes, which are located on the posterolateral or posteromedial articular border on the tip of the olecranon (Fig.…”
Section: Anatomymentioning
confidence: 99%
“…14,15,21 They are also seen in patients with a history of elbow trauma, manual laborers, or people involved in recreational activities requiring repeated forceful elbow extension. 2,3,8,12 In addition, spurs are an age-related phenomenon and can represent an incidental finding. 5 There are no data specifically on the histology of olecranon spurs; however, spur formation at other anatomic sites has been studied.…”
Section: Anatomymentioning
confidence: 99%
See 3 more Smart Citations